Analysis and research of construction methods of pre-fabricated buildings and structures for the needs of the National Defence Forces of the Republic of Kazakhstan - Sharipov A.Zh., Шарипов А.Ж. (Рroblems of engineering and professional education, 2023)
The infrastructure of the National Defence Forces of the Republic of Kazakhstan consists of 8459 buildings, 85% of which were built between 1960 and 1990. The infrastructure conditions as a whole make it possible to carry out all the tasks faced by the National Defence Forces; construction of separate military camps is not required in the nearest future. At the same time it should be specifically mentioned that a significant number of buildings and structures will require a write-off and replacement over the next 5-10 years due to their reaching service time limits.This issue is to be resolved through the construction of pre-fabricated buildings, which will significantly reduce the cost and time for construction of buildings and structures for the needs of the Armed Forces of the Republic of Kazakhstan.